Critical Integration of Emerging Technologies in Teacher Education: Looking to the Future - Jiménez-Sánchez, Susana (Revista Electrónica Educare, 2020)
Emerging technologies will be present in the educational future, for that reason at Centro de Investigación y Docencia en Educación (CIDE), from Universidad Nacional, Costa Rica, we must work from teacher training, in processes where that technologies are integrated into pedagogical practice and critical meaningful learning is achieved.